Read this paper if you want to learn logistic regression - Fernandes, Antônio Alves Tôrres; Figueiredo Filho, Dalson Britto; Rocha, Enivaldo Carvalho da; Nascimento, Willber da Silva (Revista de Sociologia e Política, 2020)
ABSTRACT Introduction: What if my response variable is binary categorical? This paper provides an intuitive introduction to logistic regression, the most appropriate statistical technique to deal with dichotomous dependent variables. Materials and Methods: we estimate the effect of corruption scandals on the chance of reelection of candidates running for the Brazilian Chamber of Deputies using data from Castro and Nunes (2014). Specifically, we show the computational implementation in R and we explain the substantive interpretation of the results. Results: we share replication materials which quickly enables students and professionals to use the procedures presented here for their studying and research activities. Discussion: we hope to facilitate the use of logistic regression and to spread replication as a data analysis teaching tool. KEYWORDS: regression; logistic regression; replication; quantitative methods; transparency.